Beyond mortality: definitions and benchmarks of outcome standards in paediatric anaesthesiology. Issue 3 (20th June 2023) - Olbrecht, Vanessa A.; Engelhardt, Thomas; Tobias, Joseph D.
Abstract : Purpose of review: The aim of this study was to review the evolution of safety and outcomes in paediatric anaesthesia, identify gaps in quality and how these gaps may influence outcomes, and to propose a plan to address these challenges through the creation of universal outcome standards and a paediatric anaesthesia designation programme. Recent findings: Tremendous advancements in the quality and safety of paediatric anaesthesia care have occurred since the 1950 s, resulting in a near absence of documented mortality in children undergoing general anaesthesia. However, the majority of data we have on paediatric anaesthesia outcomes come from specialized academic institutions, whereas most children are being anaesthetized outside of free-standing children's hospitals. Summary: Although the literature supports dramatic improvements in patient safety during anaesthesia, there are still gaps, particularly in where a child receives anaesthesia care and in quality outcomes beyond mortality. Our goal is to increase equity in care, create standardized outcome measures in paediatric anaesthesia and build a verification system to ensure that these targets are accomplished. The time has come to benchmark paediatric anaesthesia care and increase quality received by all children with universal measures that go beyond simply mortality.